Past hurts, present hurdles: Analyzing the impact of adult socioeconomic status and healthcare access on cancer screening among childhood abuse survivors - Qaidar Alizai; Azza Sarfraz; Meher Angez; Areesh Mevawalla; Odysseas P. Chatzipanagiotou; Abdulaziz Elemosho; Rida Ejaz; Kizuki Yuza; Sebastian Ekenze; Timothy M. Pawlik (PLOS Global Public Health, 2026)
Childhood abuse is associated with long-term health consequences and may influence uptake of preventive healthcare. We evaluated whether adult socioeconomic experiences and healthcare access modify the association between childhood abuse and adherence to U.S. Preventive Services Task Force (USPSTF) cancer screening guidelines. We analyzed 2020 Behavioral Risk Factor Surveillance System (BRFSS) data among respondents who answered the childhood abuse item and were eligible for colorectal (CRC; 50–74years), cervical (women 25–64years, excluding hysterectomy), and/or breast screening (women 40–74years), adapted to BRFSS 5-year age categories. Screening adherence was compared by abuse history. Survey-weighted Poisson regression estimated multivar incidence rate ratios (aIRRs), and stratified models assessed heterogeneity across adult socioeconomic factors and healthcare access. Among 123,169 respondents (weighted U.S. adult population: 68.08 million), 43.7% reported childhood abuse. Eligible cohorts included 27,368 for cervical screening and 39,986 women for breast screening (ages 40–74). In fully adjusted survey-weighted models, childhood abuse was associated with modestly lower adherence to cervical (aIRR = 0.97, 95%CI 0.94–0.99) and breast screening (aIRR = 0.96, 95%CI 0.93–0.99). In stratified analyses, inverse associations for cervical screening persisted across multiple socioeconomic strata, including college graduates (aIRR = 0.96, 95%CI 0.94–0.98), employed respondents (aIRR = 0.97, 95%CI 0.95–0.98), and married respondents (aIRR = 0.97, 95%CI 0.96–0.99). For breast screening, childhood abuse was consistently associated with lower adherence across most strata, with stronger associations among divorced/widowed/separated respondents (aIRR = 0.92, 95%CI 0.90–0.95) and lower-income respondents (aIRR = 0.95, 95%CI 0.93–0.96), and a pronounced deficit among uninsured women (aIRR = 0.86, 95%CI 0.78–0.95). Childhood abuse was associated with modestly lower adherence to cervical and breast cancer screening (with smaller, less consistent differences for CRC), and these associations varied across socioeconomic and healthcare-access strata. These findings support targeted, trauma-informed strategies to improve screening uptake among survivors of childhood abuse, particularly in settings where structural barriers to preventive care persist.